Audiovestibular Quantification in Rare Third Window Disorders in Children - Dasgupta, Soumit; Ratnayake, Sudhira; Crunkhorn, Rosa; Iqbal, Javed; Strachan, Laura; Avula, Shivaram (Frontiers in Neurology, 2020)
Third window disorders are structural abnormalities in the bony otic capsule that establish a connection between the middle/inner ear or the inner ear/cranial cavity. Investigated extensively in adults, they have hardly been studied in children. This study is a retrospective study of children (aged 5 years - 17 years) diagnosed with rare third window disorders (third window disorders reported rarely or not reported in children) in a tertiary paediatric vestibular unit in the United Kingdom. It aimed to investigate audiovestibular function in these children. Final diagnosis was achieved by high resolution CT scan of the temporal bones. Of 920 children attending for audiovestibular assessment over a 42 month period, rare third windows were observed in 8 (< 1%). These included posterior semicircular canal dehiscence (n =3, 0.3%), posterior semiciruclar canal thinning (n=2 , 0.2%), X linked gusher (n=2, 0.2%) and a combination of dilated internal auditory meatus/irregular cochlear partition/deficient facial nerve canal (n=1, 0.1%). The majority of them (87.5%) demonstrated a mixed/conductive hearing loss with an air-bone gap in the presence of normal tympanometry (100%). Transient otoacoustic emissions were absent with a simultaneous cochlear pathology in 50% of the cohort. Features of disequilibrium were observed in 75% and about a third showed deranged vestibular function tests. Video head impulse test abnormalities were detected in 50% localising to the side of the lesion. Cervical vestibular evoked myogenic potential test abnormalities were observed in all children in the cohort undergoing the test where low thresholds and high amplitudes classically found in third window disorders localised to the side of the defects in 28.5%. 71.4% in the series also demonstrated absent responses/amplitude asymmetry some of which did not localise to the ipsilesional side. 2 children presented with typical third window symptoms. This study observes 2 new rare paediatric third window phenotypes and the presence of a cochlear hearing loss in these disorders. It emphasizes that these disorders should be considered as an aetiology of hearing loss/disequilibrium in children. It also suggests that paediatric third window disorders may not present with classical third window features and are variable in their presentations/audiovestibular functions.